Investigating corruption (Philippine Center for Investigative Journalism, 2004)
This 20-minute video tells you how to catch culprits. There are laws and public documents that aid citizens in detecting corruption. There are procedures that can be followed in building strong, solid cases against public officials who betray the public trust. And there are organizations that have made headway in the fight against graft and corrutption.